Comparison of NaOH and Na2CO3 as absorbents for CO2 absorption in carbon capture and storage technology - Fadhilah Ikhsan Dinul; Hendri Nurdin; Dieter Rahmadiawan; Nasruddin; Imtiaz Ali Laghari; Tarig Elshaarani (Journal of Engineering Researcher and Lecturer, 2023)
CO2 gas is a greenhouse gas that causes global warming. Greenhouse gases are gases in the atmosphere that can absorb and reflect infrared radiation from the Earth's surface. Currently, the energy demand still depends on fossil fuels. On the other hand, CO2 emissions from burning fossil fuels continue to increase and contribute as greenhouse gases to the atmosphere. CO2 capture is an effort to reduce the burden of CO2 emissions into the atmosphere and is part of the Carbon, Capture, and Storage (CCS) protocol. The CO2 absorption process applied in the chemical industry is one of the CO2 absorptions using NaOH and Na2CO3 solutions as absorbents. This research aims to determine the effect of absorbent flow rate on the percentage of absorbed CO2. The method used in this research is the SLR (Systematic Literature Review) method to identify all available research. The absorbent flow rate variations used are 1 liter/minute, 1.5 liters/minute, 2 liters/minute, 2.5 liters/minute, and 3 liters/minute. The absorption process using NaOH absorbent is capable of absorbing CO2 gas with a maximum absorption of 95.52% and a minimum of 79.14%. Meanwhile, in the Na2CO3 absorbent, it is capable of absorbing CO2 gas with a maximum amount absorbed of 72.45% and a minimum of 35.47%.